2023
DOI: 10.1039/d2cc06618a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient acrylic acid production from formaldehyde and acetic acid over the NASICON-type catalyst

Abstract: The condensation of formaldehyde and acetic acid to acrylic acid is considered as one of the important ways for the clean and high value utilization of coal-based methanol derivatives. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Earlier literature findings have suggested that BAS and LAS coexisting could effectively boost the condensation reaction. 52,53 Furthermore, the B/L ratio indicates that polymorphic ZrO 2 has more LAS, which increases the condensation rate and second reduction process in comparison with the commercial ZrO 2 (Table 2). When the acidity and basicity of the catalyst are considered together to correlate with the catalyst performance, it is shown that higher concentrations of medium acidic and basic sites of the polymorphic ZrO 2 are more selective for condensation than for dehydration or reduction.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Earlier literature findings have suggested that BAS and LAS coexisting could effectively boost the condensation reaction. 52,53 Furthermore, the B/L ratio indicates that polymorphic ZrO 2 has more LAS, which increases the condensation rate and second reduction process in comparison with the commercial ZrO 2 (Table 2). When the acidity and basicity of the catalyst are considered together to correlate with the catalyst performance, it is shown that higher concentrations of medium acidic and basic sites of the polymorphic ZrO 2 are more selective for condensation than for dehydration or reduction.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…As versatile resin monomers, methyl acrylate (MA) and acrylic acid (AA) are widely used for the production of polymers, rubbers, adhesives, and plastics. Currently, nearly most of the MA is manufactured industrially from hydrolysis of acrylonitrile and oxidation of propylene (Scheme ). , The hydrolysis of the acrylonitrile process relies on excessive toxic hydrogen cyanide with large amounts of sulfuric acids as raw materials, leading to environmental pollution as well as a large amount of the low-valuable NH 4 HSO 4 , which has been gradually replaced by the two-step oxidation of propylene.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of Supports. To understand the properties of supports and their effects on Cs sites better, 29 Si solid-state MAS NMR and IR−OH spectroscopy were measured (Figures intensity between −103 and −113 ppm (defined as Q 3 /Q 4 ) is directly relevant with the content of Si−OH groups. 45,47 According to Table S1, Q 3 disappeared after introduction of Cs species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The selectivity of crotonaldehyde was increased to 80.4% after doping with Cu, which is much higher than that catalyzed by the primary MgAlO oxide. Gao et al synthesized NASICON catalysts for the aldol condensation of acrylic acid and revealed that the space-time yield of acrylic acid and methyl acrylate can be up to 123.9 μmol·g –1 ·min –1 . This is mainly owing to the synergistic impact of acid and base sites .…”
Section: Introductionmentioning
confidence: 99%